Effectiveness of kesgilut videos on knowledge of dental and oral health maintenance in kindergarten children at Al'fath Pasir Putih, Jambi City in 2024 - Febrianti, Sri; Tanjung, Yeni Desriwati (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2024)
Background: The behavior of Indonesian children in brushing their teeth remains low, which is attributed to a lack of knowledge on how to maintain dental and oral health. One way to improve this knowledge is through counseling, and video media is one such tool that combines two elements, sound and images, making it more effective in conveying information. This study aims to evaluate the effectiveness of video media counseling in enhancing knowledge and brushing behavior among early childhood children, starting from the kindergarten level. Method: The research uses a literature review method involving the collection, reading, and management of bibliographic data. This approach helps researchers categorize and organize various sources, leading to a deeper understanding of the research topic. Results: The study involving 16 control and 16 treatment samples from a kindergarten in Jambi revealed balanced gender distributions and similar age ranges across groups. Normality tests confirmed that the data for dental and oral health knowledge were normally distributed, justifying the use of paired and independent sample t-tests. The results showed a significant increase in knowledge scores from pre-test to post-test in both groups, with the Kesgilut video treatment resulting in a notably greater improvement compared to the control group. This indicates that the Kesgilut video was more effective in enhancing dental health knowledge. Interactive educational methods, like video and storytelling, proved to be effective tools in engaging children and improving their understanding of health practices, aligning with previous research on the benefits of such methods for young learners Conclusion: The Kesgilut video was more effective in improving dental and oral health knowledge among the kindergarten children compared to the control group.